2019
DOI: 10.1186/s12199-019-0788-6
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and lifestyle factors associated with depressive tendencies in general Japanese men and women: NIPPON DATA2010

Abstract: Background The gender-specific characteristics of individuals at an increased risk of developing depression currently remain unclear despite a higher prevalence of depression in women than in men. This study clarified socioeconomic and lifestyle factors associated with an increased risk of subclinical depression in general Japanese men and women. Methods Study participants were residents not receiving psychiatric treatments in 300 sites throughout Japan in 2010 (1152 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“… 39 Suzuki et al reported that the risk of depressive tendencies was higher in men who were not working and aged <60 years, compared with those who were working. 40 Considering that insomnia symptoms appear before anxiety and mood disorders and that chronic insomnia increases the occurrence and risk of recurrence of such disorders, 21 , 23 the outcomes for individuals with insomnia long after the earthquake must be carefully reassessed, with special attention paid to this population.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Suzuki et al reported that the risk of depressive tendencies was higher in men who were not working and aged <60 years, compared with those who were working. 40 Considering that insomnia symptoms appear before anxiety and mood disorders and that chronic insomnia increases the occurrence and risk of recurrence of such disorders, 21 , 23 the outcomes for individuals with insomnia long after the earthquake must be carefully reassessed, with special attention paid to this population.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that unemployment is one of the risk factors related to the level of depressions and suicidal behavior for men with diagnosed depressive disorder. Suzuki et al ( 28 ) proofed that the risk of depressive tendencies is significantly higher in men who were not working (OR, 3.57; 95% CI, 1.31–9.72). Evidence suggests that the risk of depression increases steadily for 6 months after the individual becomes unemployed, then reaches a plateau and is reversed almost immediately on finding work ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the causes of depressive symptoms were not considered. Interventions to decrease depressive symptoms through exercise among older adults as well as the causes of depressive symptoms, such as physical (e.g., arthritis) [34] and environmental (e.g., living alone) [35] factors should be considered. Future studies and intervention implementations should explore better daily activities and ways of motivating participants to continue daily activities to prevent depressive symptoms and memory problems.…”
Section: Discussionmentioning
confidence: 99%